CONNECTEDNESS OF Grapholita molesta (BUSCK, 1916) (LEPIDOPTERA: TORTRICIDAE) POPULATION BETWENN PEACH AND APPLE ORCHARDS - POLTRONIERI, Alex Sandro; MONTEIRO, Lino Bittencourt; SCHUBER, Joselia Maria; CARDOSO, Nério Aparecido (Scientia Agraria, 2008)
The Oriental fruit moth is an important pest of peach and apple orchards, once it is able to move among the orchards in search of hosts. The aim of this work was to check the connectedness of G. molesta population between peach and apple orchards. Pheromone traps were installed in the orchard of peaches ‘Chimarrita’ and the orchard of apples ‘Eva’ and in the orchard of peaches ‘Texano’ and the orchard of apples ‘Eva’. Connectedness was not verified among the populations of the orchards ‘Chimarrita ‘ and ‘Eva ‘, while the populations of the orchards ‘Texano ‘ and ‘Eva ‘ behaved as one.